Nanostructured carbon black for simultaneous electrochemical determination of trace lead and cadmium by differential pulse stripping voltammetry. Issue 7 (25th July 2018) - Xie, Ruigang; Zhou, Lingli; Lan, Cuiling; Fan, Fangfang; Xie, Ruifeng; Tan, Hongyu; Xie, Tiansheng; Zhao, Lingmin
Abstract : Nanostructured carbon black (CB) was first employed directly in this paper for the simultaneous electrochemical determination of trace Pb(II) and Cd(II) using differential pulse anodic stripping voltammetry. The morphology and surface properties of conductive CB were characterized by transmission electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, ultraviolet–visible spectroscopy and Raman spectroscopy. Special pore structures, as well as surface chemical functional groups, endow CB with excellent catalytic and adsorption properties. Some parameters affecting electrical analysis performance were investigated systematically including deposition time and potential, pH value of solution, volume of suspension, amount of Bi(III) and Nafion solution. CB–Nafion–glassy carbon electrode sensor linear response ranges from 6 to 1000 nM for selective and simultaneous determination. The detection limits were calculated to be 8 nM (0.9 µg l −1 ) for Cd(II) and 5 nM (1.0 µg l −1 ) for Pb(II) (S/N = 3) for the electrocatalytic determination under optimized conditions. The method was successfully used to the determination of actual samples and good recovery was achieved from different spiked samples. Low detection limits and good stability of the modified electrode demonstrated a promising perspective for the detection of trace metal ions in practical application.